INFORMATION SYSTEM DEVELOPMENT FOR JOB SCHEDULING AND PROGRESS UPDATE TO PROVIDE REAL TIME INFORMATION IN SOFT GOOD ENGINEERING DEPARTMENT, A CASE STUDY - Ayu, Ketut Gita; Wihardi, Fauzi (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
High variation in the types of toy produced in a multinational toy manufacturing company results in excessive variation in the types of soft good fabricated. A real-time and precise information flow from the release of the bill of materials (BOM) to the execution in the production floor is crucial in ensuring the smooth soft good mass production flow. On time production process of nondurable goods or so-called soft goods requires real time information of the progress update during the production of dolls costumes. The research is conducted to determine the most effective information system tool in catching delay and its cause of lateness in costume development process. The tool allows control of production system primarily in the input and process area and utilizes the earliest due date (EDD) sequencing method to minimize the maximum delay in the information transfer. Upon implementation, accurate and according-to-the-needs information is retrieved in real time which increases the efficiency of production process of the soft goods significantly.